Truncated Boolean Matrices For Dna Computation - Nordiana, Rajaee; Awang Ahmad Sallehin, Awang Husaini; Masra, S.M.W. (IJCSEA, 2014)
Although DNA computing has emerged as a new computing paradigm with its massive parallel computing capabilities, the large number of DNA required for larger size of computational problems still remain as a stumbling block to its development as practical computing. In this paper, we propose a modification to implement a physical experimentation of two Boolean matrices multiplication problem with DNA computing. The Truncated Matrices reduces the number of DNA sequences and lengths utilized to compute the problem with DNA computing.